Impact of the geriatric nutritional risk index on long-term outcomes in patients undergoing hemodialysis: a meta-analysis of observational studies - Hung, Kuo-Chuan; Kao, Chia-Li; Hsu, Chih-Wei; Yu, Chia-Hung; Lin, Chien-Ming; Chen, Hsiao-Tien; Chang, Ying-Jen; Liao, Shu-Wei; Chen, I-Wen (Frontiers in Nutrition, 2024)
Background: This meta-analysis aimed to synthesize current evidence on the association between the Geriatric Nutritional Risk Index (GNRI) and long-term outcomes in patients undergoing hemodialysis. Methods: Electronic databases were systematically searched for relevant studies that investigated the association between GNRI and long-term outcomes in hemodialysis patients until November 2023. The primary outcome was the association between the GNRI (i.e., low versus high) and overall mortality risk, while the secondary outcome was the relationship between the GNRI and cardiovascular mortality risk. Results: Thirty cohort studies involving 55,864 patients were included. A low GNRI was found to be significantly associated with increased overall mortality (hazard ratio [HR]: 2.42, 95% confidence interval [CIs]: 2.10–2.79, p<0.00001, I² = 65%). Each unit increase in GNRI corresponded to a 5% reduction in mortality risk (HR: 0.95, 95% CI: 0.93–0.96, p<0.00001, I2 = 79%). The association remained consistent across Asian (HR = 2.45, 95% CI: 2.08–2.88, p<0.00001, I² = 70%) and non-Asian subgroups (HR = 2.3, 95% CI: 1.72–3.06, p<0.00001, I2 = 23%). Meta-regression analysis of patient age (coefficient: −0.002; p = 0.896), male proportion (coefficient: 0.002; p = 0.875), percentage of diabetes mellitus (coefficient: −0.003; p = 0.605), and follow-up duration (coefficient: −0.003; p = 0.431) revealed that these moderator variables did not significantly influence the association between GNRI and overall mortality risk. Cardiovascular mortality risk also increased with low GNRI (HR, 1.93; 95%CI: 1.51–2.45, p<0.00001; I2=2%). Similarly, an inverse association was observed between the GNRI values and cardiovascular mortality risk (HR, 0.94; 95% CI: 0.91–0.97; p < 0.0001; I2 = 65%) (per unit increase). Conclusion: The GNRI is a simple nutritional screening tool that can be used to effectively stratify patients undergoing hemodialysis globally. Further studies are warranted to determine whether nutrition optimization based on the GNRI improves long-term outcomes.